Effects of urban green belts on the air temperature, humidity and air quality - Zhu, Chunyang; Ji, Peng; Li, Shuhua (Journal of Environmental Engineering and Landscape Management, 2017)
As urbanization increases, designing green space that offers ecological benefits is an increasingly important goal of urban planning. As a linear green space in an urban environment, green belts lower air temperature, increase relative humidity, and improve air quality. To quantify the ecological effects of urban green belts and to identify a critical width for effective urban green belts, we analysed the width of urban green belts in terms of their effects on air temperature (T), relative humidity (RH), concentration of negative air ions (NAI) and bacteria rate (BR). The air T, RH and NAI from 8:00 to 18:00 and BR at 9:00 over seven days were investigated on six widths of green belts (0–10 m, 10–20 m, 20–30 m, 30–40 m, 40–50 m and over 50 m) along the west Fourth Ring Road of Beijing in April, July, October and December 2009. We found that (1) the T-RH benefits increased with the width of the green belts, and the 6 m belt had the smallest effect on T-RH, followed by the 16 m and 27 m belts, whereas the effect was obvious with the 34 m belt and conspicuous and stable with the 42 m belt (approximately 80% green coverage) (P < 0.05); (2) the critical width reference value of urban green belts for an obvious effect on the increase in NAI concentration was approximately 42 m (approximately 80% green coverage) (P < 0.05) and the NAI concentration increased with the width of green belts even in July; and (3) the positive effect on the decrease in the BR was greater than the negative effect, the BR decreased with the green belt width and the changes in the brs were stable with the 34 m belt. The results of this study may help urban planners and designers achieve urban green space designs that optimize ecological effects and cultural benefits.